1989
DOI: 10.1002/mpo.2950170220
|View full text |Cite
|
Sign up to set email alerts
|

Testicular relapse in adult acute lymphocytic leukemia: A case report and literature review

Abstract: In the pediatric age group, acute lymphocytic leukemia (ALL) may involve the testicles during complete remission of the disease in the marrow. We report a case of testicular involvement with ALL in an adult and review 11 cases of this phenomenon reported previously, to draw attention to the fact that it can occur at any age. Recognition of this fact is important, because testicular involvement may be the first manifestation of systemic relapse. The treatment of choice is irradiation to both testicles and combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…The incidence may be higher in certain populations depending on genetic and treatment-related characteristics 7. While ITR during complete remission of leukaemia has been reported in children, the reports in adults are rare and may represent first sign of systemic relapse 8–10. Studies have shown persistence of isolated microscopic testicular leukaemia after completion of initial treatment which is disconcerting 9.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence may be higher in certain populations depending on genetic and treatment-related characteristics 7. While ITR during complete remission of leukaemia has been reported in children, the reports in adults are rare and may represent first sign of systemic relapse 8–10. Studies have shown persistence of isolated microscopic testicular leukaemia after completion of initial treatment which is disconcerting 9.…”
Section: Discussionmentioning
confidence: 99%
“…data]. There are 12 cases reported in the literature [7], only one was in a case reported as having a cytogenetically ab normal clone in the bone marrow at diagnosis. The pre sent case is the first report in adult Ph ALL.…”
Section: Discussionmentioning
confidence: 99%
“…This has been described mainly in the pediatric age group, with a reported incidence between 0.5% and 2% [1] and overall 5-year survival of adult patients aged 18-60 years with ALL is 20-35% [2]. There are no statistical data for the testicular relapse of ALL in adults [3,4].…”
mentioning
confidence: 99%